The Gut Microbiome (IntechOpen, 2023)
In the last decades, the importance of gut microbiome has been linked to medical research on different diseases. Developments of other medical disciplines (human clinical pharmacology, clinical nutrition and dietetics, everyday medical treatments of antibiotics, changes in nutritional inhabits in different countries) also called attention to study the changes in the gut microbiome. This book contains five excellent review chapters in the field of gut microbiome, written by researchers from the USA, Canada, China, and India. These chapters present a critical review about some clinically important changes in the gut microbiome in the development of some human diseases and therapeutic possibilities (liver disease, cardiovascular diseases, brain diseases, gastrointestinal diseases). The book brings to attention the essential role of gut microbiome in keeping our life healthy. This book is addressed to experts of microbiology, podiatrists, gastroenterologists, internists, nutritional experts, cardiologists, basic and clinical researchers, as well as experts in the field of food industry.